Exploring the contribution of spatial navigation to cognitive functioning in older adults - Laczó, Jan; Andel, Ross; Nedelska, Zuzana; Vyhnalek, Martin; Vlcek, Kamil; Crutch, Sebastian; Harrison, John; Hort, Jakub (Neurobiology of aging, 2017)
Spatial navigation (SN) impairment is present early in Alzheimer's disease (AD). We tested whether SN performance, self-centered (egocentric) and world-centered (allocentric), was distinguishable from performance on established cognitive functions-verbal and nonverbal memory, executive and visuospatial function, attention/working memory, and language function. 108 older adults (53 cognitively normal [CN] and 55 with amnestic mild cognitive impairment [aMCI]) underwent neuropsychological examination and real-space navigation testing. Subset (n = 63) had automated hippocampal volumetry. In a factor analysis, allocentric and egocentric navigation tasks loaded highly onto the same factor with low loadings on other factors comprising other cognitive functions. In linear regression, performance on other cognitive functions was not, or was only marginally, associated with spatial navigation performance in CN or aMCI groups. After adjustment for age, gender, and education, right hippocampal volume explained 26% of the variance in allocentric navigation in aMCI group. In conclusion, spatial navigation, a known cognitive marker of early AD, may be distinguished from other cognitive functions. Therefore, its assessment along with other major cognitive functions may be highly beneficial in terms of obtaining a comprehensive neuropsychological profile.
Keywords: Magnetic Resonance Imaging; Spatial navigation; magnetická rezonanční tomografie; Humans; lidé středního věku; Spatial Navigation; Mild cognitive impairment; kognice; paměť; Female; Aged; stárnutí; Hippocampus; Morris Water Maze; senioři; lidé; Aging; hipokampus; ženské pohlaví; Male; Middle Aged; Aged, 80 and over; Alzheimer's disease; senioři nad 80 let; Memory; prostorová navigace; mužské pohlaví; Cognition; Neuropsychology